Studi Tingkat Kenyamanan Jalur Pedestrian di Kawasan Perdagangan Jalan Somba Opu Makassar - Siti Nurafifah Asis; Kamran Aksa; Rimba Arief (Journal of Urban Planning Studies, 2022)
The purpose of this study was to determine the comfort level of pedestrian paths in the Somba Opu Makassar trading area. This study uses a quantitative method to answer the comfort level of pedestrian paths in the Somba Opu Makassar street trading area. Data collection is carried out through observation, documentation and questionnaires, where the sample is taken using simple random sampling. The data obtained were then analyzed using descriptive analysis and correlation analysis. This research is the result of descriptive and correlation methods using data collection techniques from observations, and documentation of pedestrian paths in the Jalan Somba Opu Makassar trade area whose instruments are based on the Targets of the Minister of Public Works Regulation No. 02/SE/M/2018 concerning Technical Planning for Pedestrian Facilities .